TOLL BOOTH QUEUING SIMULATION USING PHP PROGRAMMING LANGUAGE - Manik, Ngarap Im (Universitas Bunda Mulia, 2020)
The purpose of this research is to examine the minimum service standard in Pondok Ranji tollgate transaction by simulating tollgate traffic data available using a web-based application using PHP. This research also aims to determine whether the queue in Pondok Ranji tollgate occurred because of the transaction performance that does not satisfy the minimum service standard. The first in first out queuing characteristic is one of the commonly used queuing nature found in many real-life situations, where the first customer is being served first by the system before moving on to the next customer. This specific queuing characteristic is found in tollgate queuing systems. The simulation result shows that the transaction has fully satisfied the minimum service standard. In conclusion, the transaction that occurred in Pondok Ranji tollgate has satisfied the minimum service standard, therefore eliminating the possibility that queues that occurred in the tollgate happened because of the transaction process.